Florida's Organo-Auxin Herbicide Rule - 2007 - Frederick M. Fishel; Jason A. Ferrell; Gregory E. MacDonald; Barry J. Brecke (EDIS)
Revised! SS-AGR-12, a 5-page fact sheet by F.M. Fishel, J.A. Ferrell, G. E. MacDonald, and B. J. Brecke, clarifies and disseminates this rule enacted by the Florida Department of Agriculture and Consumer Services to growers and applicators. Includes a table of sources to buy wind meters. Published by the UF Department of Agronomy, June 2007.